2012
DOI: 10.1073/pnas.1215849110
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal barrier dysfunction links metabolic and inflammatory markers of aging to death in Drosophila

Abstract: Aging is characterized by a growing risk of disease and death, yet the underlying pathophysiology is poorly understood. Indeed, little is known about how the functional decline of individual organ systems relates to the integrative physiology of aging and probability of death of the organism. Here we show that intestinal barrier dysfunction is correlated with lifespan across a range of Drosophila genotypes and environmental conditions, including mitochondrial dysfunction and dietary restriction. Regardless of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

45
764
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 520 publications
(814 citation statements)
references
References 41 publications
45
764
3
2
Order By: Relevance
“…Maintaining insulin sensitivity by eliminating chronic low-grade inflammation (which may be the result of MT) could support muscle repair and regeneration, thus aiding the maintenance of muscle mass and function in aging. Invertebrate studies support this direct link between intestinal barrier function and physical function, muscle mass, and myocyte apoptosis (Rera et al, 2012;Ulgherait et al, 2014). Means with standard errors of the mean presented in parentheses are shown Stehle et al reported that greater MT was associated with worsening physical function in older people and that this relationship was also independent of inflammatory cytokines (Stehle et al, 2012), consistent with results from the current study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Maintaining insulin sensitivity by eliminating chronic low-grade inflammation (which may be the result of MT) could support muscle repair and regeneration, thus aiding the maintenance of muscle mass and function in aging. Invertebrate studies support this direct link between intestinal barrier function and physical function, muscle mass, and myocyte apoptosis (Rera et al, 2012;Ulgherait et al, 2014). Means with standard errors of the mean presented in parentheses are shown Stehle et al reported that greater MT was associated with worsening physical function in older people and that this relationship was also independent of inflammatory cytokines (Stehle et al, 2012), consistent with results from the current study.…”
Section: Discussionsupporting
confidence: 89%
“…Intestinal Bleakiness^occurs with advancing age across many species (Ma et al, 1992;Rera et al, 2012;Tran and Greenwood-Van Meerveld, 2013;Ghosh et al, 2014), but only recently has become recognized as an important mediator of healthspan, lifespan, and insulin signaling in invertebrates (Rera et al, 2012;Ulgherait et al, 2014). A Bleaky^mucosa allows greater translocation of microbial antigens into the intestinal wall and portal circulation, inciting inflammation both locally and remotely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This gap is due in part to the difficulty of measuring causes of mortality in the standard animal models in aging studies. For example, age‐related morbidity and causes of mortality in the commonly studied models of aging range from the not well understood (and often not studied) in mice (Simms & Berg, 1957; Snyder, Ward & Treuting, 2016), to the poorly understood in flies and worms (but see Herndon et al., 2002; Rera, Clark & Walker, 2012), to nonexistent in yeast. In addition, many diseases important to human aging (e.g., cardiovascular disease and dementia) do not develop spontaneously in our commonly studied model organisms.…”
Section: Introductionmentioning
confidence: 99%